(untitled) (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
Mining sector investment often presents a dilemma between economic growth and environmental sustainability. This paper discusses the strategic role of PT. Timah Tbk in building a sustainable economy and supporting the achievement of Sustainable Development Goals (SDGs) in the Bangka Belitung Islands Province. Through a qualitative-descriptive approach, this study explores the extent to which the investments made not only drive local economic growth but also address socio-ecological challenges in the operational area. The results of the study show that PT. Timah has contributed to the economic and social aspects through the provision of employment, education support, and health and community empowerment programs. However, environmental damage, inequality of benefits, and low community involvement indicate that the integration of SDGs principles still needs to be strengthened. A transformation of the investment model is needed to be fairer, participatory, and environmentally friendly to ensure that the resulting development is inclusive and sustainable in the long term.